(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2017)
This article presents a research about the design of a methodology to be implemented in a CRM tool, in order to attract and retain students in public universities. For this purpose, field work was carried out, designing a support instrument to perceive the reason for the increase in student desertion. The results showed that the customer service provided by university employees was a key factor in this. In the study carried out, several models and methodologies focused on customer service were found, seeing this as a key and fundamental axis of any organization; however, everything was focused on commercial companies. In Colombia, four universities have carried out these implementations: Universidad de Antioquia (Antioquia), Universidad Tadeo Lozano (Bogotá), Universidad del Norte (Barranquilla) and Universidad de Santander (Santander), however, these implementations have been purely administrative. It is therefore proposed to carry out an implementation focused on student recruitment and loyalty processes. In the design of the methodology, the student is defined as "Client", and the University as "Company", to make the CRM comparison. Exploratory and descriptive methodology was used, and the analysis was quantitative. A methodology was designed for its implementation in a CRM tool.